#### Answer

$6y-27$

#### Work Step by Step

$=5(2y-6)-(4y-3)$
$=5\times2y-5\times6-4y-(-3)$
$=10y-30-4y+3$
$=6y-27$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$6y-27$

$=5(2y-6)-(4y-3)$
$=5\times2y-5\times6-4y-(-3)$
$=10y-30-4y+3$
$=6y-27$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.